FAKTOR-FAKTOR DALAM UPAYA MENGATASI ABRASI DI PESISIR PANTAI DI WILAYAH KABUPATEN MERAUKE - Ransta Lewina Lekatompessy; Edoardus E. Maturbongs (Dialogue : Jurnal Ilmu Administrasi Publik, 2021)
Environmental degradations are generally caused by two factors: natural occurrences and human interference. One of the environmental damage is the occurrence of abrasion along the coast. This study aims to describe the factors that need to be considered to overcome coastal abrasion in the Merauke Regency area. The research was conducted in Merauke Regency using primary and secondary data which were then presented in a descriptive qualitative manner. The results of this study indicate that the level of coastal abrasion in Merauke Regency is of great concern. Abrasion not only causes damage to nature but also causes damage to other public facilities such as roads and public housing. To prevent the spread of abrasion, factors supporting prevention efforts are required, including economic, ecological, social, political, and cultural factors. Some of these factors are expected to be a source of concern for decision-makers to make environmental policies to overcome abrasion in Merauke Regency.